Design Optimization of Reflectarray Antenna Fabricated above Paper Based Substrate Materials - Malik, Hasan Ijaz; Ismail, Muhammad Yusof; Mokhtar, Muhammad Hezri (International Journal of Integrated Engineering, 2019)
A novel combination of X – band reflectarray antenna printed above paper based substrate material has been presented for microwave antenna application. Paper substrate materials with controlled compositions, characterized using dielectric probe shows dielectric constants of 1.68 and 1.74 and loss tangents of 0.074 and 0.082 respectively. Reflectarray unit elements simulated using CST MWS were fabricated over the paper substrates using adhesive copper tape. The fabricated samples tested for the scattering parameters demonstrate an efficient bandwidth of 340 and 290 MHz for both the substrate materials. Moreover the measured reflection phase of the elements covers a phase range of 310º and 290º for proposed paper substrates.